Crack monitoring using multiple smart materials; fiber-optic sensors & piezo sensors - Maheshwari, Muneesh (2018)
This article focuses on health monitoring of structures using multiple smart materials. In this research, two fiber-optic sensors, namely fiber Bragg grating (FBG) and fiber-optic polarimetric sensor (FOPS), are investigated for damage detection in the beam specimen. FBG is used for local strain measurement while FOPS is used for global strain measurement. Both FBG and FOPS show significant changes in the strain due to damages in the specimen. Also, at the center of the specimen, piezoelectric wafer active sensor (PWAS) is attached. The electromechanical admittance (EMA) signature of the specimen beam is recorded by PWAS. The changes in the amplitudes of the peaks obtained at various frequencies in this EMA signature are analyzed, and it is shown that the peak amplitudes respond differently to damages and to change in loading. Thus, multiple smart materials (FBG, FOPS, and PWAS) are used to get improved information on the health of the beam.